Respuesta :

The choices are missing, but we can find the right answer by using the given function

The inverse of  [tex]y=2^{3x}+1[/tex]  is  [tex]y=\frac{1}{3}[\frac{log(x-1)}{log(2)}][/tex]

Step-by-step explanation:

Let us revise the steps of finding the inverse of a function

  1. Write the function in the form of y = f(x)
  2. Switch x and y
  3. Solve to find the new y

∵ [tex]y=2^{3x}+ 1[/tex]

- Switch x and y

∴ [tex]x=2^{3y}+1[/tex]

- Subtract 1 fro both sides

∴ [tex]x-1=2^{3y}[/tex]

- Insert ㏒ in both sides

∴ [tex]log(x-1)=log(2^{3y})[/tex]

- Remember [tex]log(a^{n})=n.log(a)[/tex]

∵ [tex]log(2^{3y})=(3y).log(2)[/tex]

∴ [tex]log(x-1)=(3y).log(2)[/tex]

- Divide both sides by ㏒(2)

∴ [tex]\frac{log(x-1)}{log(2)}=3y[/tex]

- Divide both sides by 3

∴ [tex]\frac{1}{3}[\frac{log(x-1)}{log(2)}]=y[/tex]

- Switch the two sides

∴ [tex]y=\frac{1}{3}[\frac{log(x-1)}{log(2)}][/tex]

The inverse of  [tex]y=2^{3x}+1[/tex]  is  [tex]y=\frac{1}{3}[\frac{log(x-1)}{log(2)}][/tex]

Learn more:

You can learn more about the logarithmic function in brainly.com/question/11921476

#LearnwithBrainly

ACCESS MORE